The status quo of building codes and construction practices in Somaliland: practitioners' perceptions - A. Sheikh, Ahmed; F. Fakunle, Funke; A. Fashina, Adebayo (SPC Journal of Environmental Sciences, 2020)
For several years, building codes have been perceived as one of the significant ways of establishing building quality, environmental protection, public health and safety, and energy efficiency in the building and construction industry. Conversely, some least developing countries like Somaliland are yet to adopt and enforce the current building codes and as such allowing the construction of buildings that do not meet the minimum international standards on public health and safety. Consequently, this paper seeks to review the overall and genuine picture about Somaliland 's building traditions, history, and advancement alongside the construction practices in Somaliland. In addition, unstructured interviews were held with some top governmental officials from the Ministry of Housing and Public Works, Ministry of Environment & Rural Development, the Somaliland Fire Agency, and Hargeisa Regional Court to carefully explore the status quo of building codes in Somaliland. This was achieved by generating qualitative data via the use of open-ended questions. The findings from the study revealed that there are currently no building codes or regulations in Somaliland. Meaning that the building industry is presently self-governed by the owners and the construction professionals. The study concludes that in spite of the absent of building codes and regulations, there have been a rapid development in the building and construction industry and the increase of mid-rise building of four to six story buildings in Somaliland.Â Â